2014
DOI: 10.5455/2320-6012.ijrms20140248
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in hospitalised patients; a real concern in surgical outcomes

Abstract: Background: Lack of appropriate nutritional support during hospitalization may worsen patients' nutritional status and increases risk for infection, organ failure, decreased wound healing and suboptimal response to regular medical treatment. The prevalence and intensity of hospital malnutrition have been recognized as an important parameter in the outcome of disease. The study aimed at to determine incidence of malnutrition in hospitalized patients, the change in nutrition status during hospital stay and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
4
10
1
2
Order By: Relevance
“…Dietary counseling for each and every patient is required to avoid hospital-induced malnutrition in surgical wards. [13] Most of the patients were satisfied with the services provided by the various diagnostic centers. The less number of physiotherapies indicates that very few patients are referred to that facility.…”
Section: Discussionmentioning
confidence: 92%
“…Dietary counseling for each and every patient is required to avoid hospital-induced malnutrition in surgical wards. [13] Most of the patients were satisfied with the services provided by the various diagnostic centers. The less number of physiotherapies indicates that very few patients are referred to that facility.…”
Section: Discussionmentioning
confidence: 92%
“…Seven studies evaluated longitudinal changes in measures of nutritional status during hospitalisation, including two studies each in general, surgical, and critically ill populations and one study in patients with cancer [22,30,59,69,75,76,94].…”
Section: Change In Prevalence During Hospitalisationmentioning
confidence: 99%
“…In a prospective study of 70 surgical patients from a tertiary care hospital in India, Mahakalkar et al [59] reported that the prevalence of malnutrition according to BMI increased from 36% at the time of admission to 51% at discharge. Consistent with this finding, Young et al [69] reported significant weight loss during hospitalisation in 48 Vietnamese surgical patients; mean weight declined from 47.2 ± 8.7 kg at admission to 45.2 ± 8.4 kg at discharge (mean difference, À2.0 ± 1.6 kg; p < 0.001).…”
Section: Change In Prevalence During Hospitalisationmentioning
confidence: 99%
“…Beslenme yetersizliği cerrahi hastalarında ciddi sonuçlara sebep olmaktadır. En önemli sonuçlar arasında; yara iyileşmesinde yavaşlama, komplikasyonlarda artış, hastanede kalış süresinde uzama, morbidite, mortalite oranlarında ve bakım maliyetlerinde artma sayılabilir (1,2,5,6,8,9). Beslenme yetersizliği, hastalık sürecini etkileyen ciddi bir faktör olduğundan, beslenme ve metabolik destek, hasta bakımının sürekli ve önemli bir parçası olmalıdır (10,11).…”
Section: Introductionunclassified